Understanding The Openness of Interpersonal Communication Between Parents and Children in The Use of Smartphone for Love Relationship - NUR YUMALIA HAYUNINGTYAS; Dr. Dra. Sri Budi Lestari, SU (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
Smartphone is not only needed by adults, but also needed by teenagers. Smartphone has many functions and advantages such as making the process of communication easier between persons. This research aims to describe how children are open to their parents related to their relationship to special persons of them via smartphone. This research is also a qualitative research with phenomenology approach which tries to explore and understand how smartphone is used in keeping the interpersonal communication between parents and children opened and with no secret. And so, the method of this research is a direct and deep interview with the research subject. The result of this research is the first, child is still closed to parents about dating relationship they have. They tend to pick and choose what is told to parents, even one of them take advantage of the smartphone to communicate with a boyfriend without their parents knowing. The second is the closing of the child makes the parents actively communicating to children to find out any activities outside the home study, go about his personal life. Closing of the child is also triggered by the advice parents to focus on school first, so they were reluctant to talk about his personal life.